Kisah Teladan Kaum Perempuan di Seputar Al-Qur’an: Sebuah Inspirasi dalam Membentuk Pendidikan Karakter - Anisah Indriati (AN NUR: Jurnal Studi Islam, 2015)
Women have become the object of endless study from time to time. The issue of women is always interesting to be discussed. Women have a very important role in developing culture. History has noted that the role of women in the public sphere can not be ignored. Many women who have recorded the history of the role that continues to be fought in the midst dominated Adam. Both in the public and in the domestic sphere. The role of women in building an educated nation could not be ignored. Women have a vital role in determining the development level of a nation. Likewise in the case of education. Many stories have been recorded examples in history to take lessons. Unfortunately, the story is often ignored or even be forgotten. This article examines the stories of exemplary women who described the Qur’an. The Qur’an has been asserted that women also have a role similar to that of men. It also confirms that women can compete well in politics, freedom of opinion, independence in economic / career and also the right to education. Affirmation of the Qur’an has been proven that women have the ability and also the same rights as men. From the affirmation of the Qur’an is it clear, that the Qur’an upholds the dignity of women that still continues ignored